Analysis of Factors Triggering Impulsive Buying Among Culinary Tourists at the Rahma Waterpark Semedo Cafeteria, Tegal Regency - Dinda Maryani Ulva; Khashilan Ditiya Auvaro; Makmur Sujarwo (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to explore and explain in depth the environmental factors and psychological phenomena that trigger impulse buying behavior in culinary tourism visitors at the Rahma Waterpark Semedo Canteen, Tegal Regency. The approach used in this study was qualitative with an analytical descriptive method. Primary data collection was carried out through direct observation and in-depth interviews with canteen owners and 38 visitor informants who were selected using purposive sampling techniques. Data analysis is applied using a flowing model that includes data reduction, data presentation, and conclusion drawn. The results of the study showed that the majority of visitors were dominated by large family groups and elementary school children who made sudden transactions while resting. The most consistent external factors driving tourists' spontaneous shopping decisions are the atmosphere of the canteen environment that is clean and family-friendly, as well as sensory marketing in the form of the strong aroma of cuisine through the open canteen layout. This combination of stimuli successfully builds a comfortable mood (positive affect), thus loosening cognitive control and collapsing the shopping rationality of visitors in order to get instant emotional satisfaction at tourist sites.